1961
DOI: 10.1021/jf60113a015
|View full text |Cite
|
Sign up to set email alerts
|

Butter Adulteration, Detection of Hydrogenated Fats in Butter Fat by Measurement of cis-trans Conjugated Unsaturation

Abstract: Use of the 5-liter modified Schóniger combustion flask has been extended to the combustion of potatoes, cherries, onions, cabbage, and oats for the determination of residues of arsenic, bromide, chloride, manganese, and nickel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The CLAs are a mixture of positional and geometric isomers of linoleic acid (9c,12c C18:2), which were first identified in rumen fluid as an intermediate of the biohydrogenation process (Bartlett & Chapman, 1961). In synthetic CLA preparations the 9c,11t and 10t,12c isomers are predominant (often in a 1:1 ratio; Larsen, Toubro, & Astrup, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The CLAs are a mixture of positional and geometric isomers of linoleic acid (9c,12c C18:2), which were first identified in rumen fluid as an intermediate of the biohydrogenation process (Bartlett & Chapman, 1961). In synthetic CLA preparations the 9c,11t and 10t,12c isomers are predominant (often in a 1:1 ratio; Larsen, Toubro, & Astrup, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the anticarcinogenic potential of CLA was not understood until it was isolated as a mutagenic modulator activity in fried ground beef (26). CLA has also been isolated from raw ground beef, various natural and processed cheeses (27), and butterfat (28). Nine isomers of CLA have been identified; four of these, c-9,Ml-; M0,c-12-; f-9,Ml-; and M0,f-12-octadecadienoic acids, account for >89% of total CLA (27).…”
Section: Introductionmentioning
confidence: 99%
“…Although the biochemistry of CLA has been documented for decades in the literature, little is known about its nutritional activity or requirement (3). More than 30 years ago, Bartlett and Chapman (4) first reported that CLA was an intermediate in the microbial biohydrogenation of linoleic acid in butter fat. Kepler and associates (5) subsequently discovered that a rumen bacterium, Butyrivibriojlbrisolvens, was able to convert linoleic acid to stearic acid via CLA.…”
Section: Introductionmentioning
confidence: 99%